Estudos para uma proposta de feedback de suavização e prolongamento da fala da pessoa que gagueja - Ferreira, Astrid Mühle Moreira (2019)
The purpose of this thesis is to develop a proposal of a modeling of speech fluency of people who stutter (PWS) through feedbacks of the speech sounds’ visual representation. Therefore, two studies were carried out with the following purposes: (1) analysis of physiological, acoustic and perceptual data of PWS´s speech; and (2) development of a proposal of fluency shaping strategies as a stimulus bank for the development of a technological biofeedback resource for speech sounds visual representation during the execution of fluency shaping exercises. In study 1, 10 PWS, from the research group (RG) speech samples were analyzed from two collections, one performed before and the other immediately after a brief experimental fluency shaping intervention. Samples from the first collection were compared to samples from 10 fluent-speaking of control group (CG), paired by sex and age. The analyses were conducted by physiological (indirect subglottic pressure measurements), acoustic (ExpressionEvaluator measurements: f0, f0 derivative, intensity, spectral decline and long-term spectrum) and perceptual (Vocal Profile Analysis Scheme) means. The results served as a basis for the development of the study 2, which included: analysis of software and websites; development of word stimulus framework; requirements structure; and recordings of smooth prolonged speech samples, acoustically analyzed to determine feedback parameters of software fluency modeling targets. It was possible to conclude that the survey of perceptual and acoustic characteristics of PWS speech reveals particularities in relation to RG. The immediate application of the fluency shaping brief intervention implied variations in speech patterns, with a tendency to decrease effort. This decrease was expressed by measures of physiological of subglottic pressure, of acoustics f0 domain and intensity, and of perceptual analysis of infra and supraglottic. These findings justify the requirements incorporated into the draft speech modeling feedback proposal. And the results support an integrated conception work of a speech biofeedback system with the incorporation of speech stimulus, whose intensity and duration measures were able to collaborate to its development, in a gamified structure format, enabling the frequent stimulation possibility of the fluency shaping of PWS